1993
DOI: 10.3171/jns.1993.78.1.0036
|View full text |Cite
|
Sign up to set email alerts
|

The natural history and management of symptomatic and asymptomatic vertebral hemangiomas

Abstract: Fifty-nine cases of vertebral hemangioma were seen at the Mayo Clinic between 1980 and 1990. Vertebral hemangiomas were discovered incidentally in 35 patients, while pain was the presenting complaint in 13 patients. Five patients presented directly with progressive neurological deficit requiring surgery, and six patients had surgery elsewhere for spinal cord compression and were referred for follow-up evaluation. To better define the natural history of these lesions, a historical review of these patients was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
299
1
27

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(329 citation statements)
references
References 42 publications
1
299
1
27
Order By: Relevance
“…Histopathology, immunohistochemistry, and electron microscopy show that all lesions are identical regardless of location [12]. Whereas spinal osseous cavernous malformations are highly vascular lesions with a high risk of massive intraoperative blood loss [9,12], intramedullary and intracerebral CAs are angiographically occult [1,2,8,12,13,17] and can be resected with negligible blood loss.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Histopathology, immunohistochemistry, and electron microscopy show that all lesions are identical regardless of location [12]. Whereas spinal osseous cavernous malformations are highly vascular lesions with a high risk of massive intraoperative blood loss [9,12], intramedullary and intracerebral CAs are angiographically occult [1,2,8,12,13,17] and can be resected with negligible blood loss.…”
Section: Discussionmentioning
confidence: 94%
“…In 2002, Nagib and O'Fallon [14] summarized nine cases including their two personal cases, and in 2006, Bakir et al [3] reported another pediatric patient with ImCA: Although the number of reported pediatric cases with ImCA is small, we can outline some differences from that of the While ImCA in the adult occur more frequently in women than in men [12,17], with a female/male ratio of approximately 2:1, seven of ten cases of symptomatic ImCA reported in children were male, thus accounting for a male/ female ratio of 2:1. The hypothesis of a hormonal effect leading to a greater risk of bleeding in female adults does not seem to be verified in children, but the mean age at bleeding is 13.2 years (range [8][9][10][11][12][13][14][15][16][17] and can also suggest the hormonal influence of puberty.…”
Section: Special Features Of Imca In Childrenmentioning
confidence: 99%
“…CT is the procedure of choice for patients with symptomatic hemangiomas, as it determines the extent of the lesion and the site of compression, if present, and it reveals lesions in other vertebrae that an X-ray may have failed to demonstrate [26,32,38]. Magnetic resonance imaging (MRI) is useful, especially in differentiating a hemangioma from other tumors; it is valuable in pre-operative planning and it can provide additional information regarding the aggressiveness of the lesion [14,27]. Spinal angiography is a useful diagnostic tool, especially in pre-operative planning, since it can demonstrate both the vascularity of the lesion and the origin of the feeding vessels [1,11,17,30].…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the available literature has failed to locate any other reports of similar cases. Fox and Onorfio [14] reported six cases of multiple lesions (two to five affected vertebrae), but there is no information regarding pain pattern or alterations in clinical presentation between the various stages of followup. In addition, we found no report regarding the prognosis of the patient with multiple involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation